Literature Study: Application of PhET Simulation-Assisted PBL Learning Module to Improve Students' Creative Thinking Skills - Yani Martia Lestari; Tugiyo Aminoto; Erlida Amnie (Kappa Journal, 2025)
This study aims to review the effectiveness of the PBL model combined with the simulation of PhET in improving students' creative thinking skills on alternative energy materials. The study was conducted through a review of 19 selected articles from 49 relevant studies, based on the suitability of the research variables, the quality of the journals, and the clarity of the methodologies. The analysis showed that PBL improved students' learning outcomes, concept understanding, and creativity, while the PhET simulation helped visualise abstract concepts interactively. However, few studies have developed specialised PBL-based modules integrated with PhET to train creative thinking on alternative energy topics. Therefore, this study provides novelty by emphasising the importance of the direction of development of PBL-PhET modules as innovative teaching materials that support the learning needs of the 21st century.